Debt Sustainability in Low-Income Countries : Policies, Institutions, or Shocks? - Bal Gunduz, Yasemin (IMF Working Papers; Working Paper ;, 2017)
This paper estimates the determinants of external debt distress in low-income countries (LICs), disentangling the roles of institutions, shocks, and policies. The most prominent factors in raising the risk of debt distress are the weak protection of private property rights, adverse shocks to real non-oil commodity prices, and a high debt burden. Results also suggest that weak economic institutions tend to raise the probability of debt distress through persistently weak economic policies and high vulnerability to external shocks. The model enables a more granular analysis of debt sustainability in LICs and has a higher predictive power compared to the earlier scant literature.